Synthesis of 9,10-bis(hydroxyimino)-4,8,11,15-tetraaza-1,2,17,18-o-dicyclopentylideneoctadeca ne and its complexes with Co(II), Co(III), Cu(II) and Ni(II) - Çukurovali, A.; Taş, E. (My University, 1999)
A novel dioxime 9, 10-bis(hydroxyimino)-4,8,11,15-tetraaza-1,2,17,18-O-dicyclopentylideneoctadecane (LH2) was prepared by the reaction of 1,2-O-dicyclopentylidene-4-aza-7-aminoheptane and (E,E) dichloroglyoxime in THF. Mononuclear complexes with a metal-ligand ratio of 1:2 were prepared with Co(II), Cu(II) and Ni(II). An octahedral Co(III) complex of the ligand was prepared with pyridine (py) and chloride ion as axial ligands. The authenticity of the ligand and its complexes was established by elemental analyses, IR, 1H and 13C NMR spectra, magnetic susceptibility measurements, thermogravimetric analyses (TGA) and differential thermal analyses (DTA).
Keywords: 1,3-dioxolane; Cobalt(II and III); Copper(II); Nickel(II) complexes; Synthesis; Vic-dioxime